Cobaloxime Complex Salts: Synthesis, Patterning on Carbon Nanomembranes and Heterogeneous Hydrogen Evolution Studies. Issue 68 (17th November 2021) - Oswald, Eva; Gaus, Anna‐Laurine; Kund, Julian; Küllmer, Maria; Romer, Jan; Weizenegger, Simon; Ullrich, Tobias; Mengele, Alexander K.; Petermann, Lydia; Leiter, Robert; Unwin, Patrick R.; Kaiser, Ute; et al.
Abstract: Cobaloximes are promising, earth‐abundant catalysts for the light‐driven hydrogen evolution reaction (HER). Typically, these cobalt(III) complexes are prepared in situ or employed in their neutral form, for example, [Co(dmgH)2 (py)Cl], even though related complex salts have been reported previously and could, in principle, offer improved catalytic activity as well as more efficient immobilization on solid support. Herein, we report an interdisciplinary investigation into complex salts [Co(dmgH)2 (py)2 ] + [Co(dmgBPh2 )2 Cl2 ] −, TBA + [ Co ( dmgBPh 2 ) 2 Cl 2 ] - and [Co(dmgH)2 (py)2 ] + BArF − . We describe their strategic syntheses from the commercially available complex [Co(dmgH)2 (py)Cl] and demonstrate that these double and single complex salts are potent catalysts for the light‐driven HER. We also show that scanning electrochemical cell microscopy can be used to deposit arrays of catalysts [Co(dmgH)2 (py)2 ] + [Co(dmgBPh2 )2 Cl2 ] −, TBA + [ Co ( dmgBPh 2 ) 2 Cl 2 ] - and [Co(dmgH)2 (py)Cl] on supported and free‐standing amino‐terminated ∼1‐nm‐thick carbon nanomembranes (CNMs). Photocatalytic H2 evolution at such arrays was quantified with Pd microsensors by scanning electrochemical microscopy, thus providing a new approach for catalytic evaluation and opening up novel routes for the creation and analysis of "designer catalyst arrays", nanoprinted in a desired pattern on a solid support. Abstract : We report the synthesis of a new cobaloxime‐based double complex salt and its use as a catalyst for the homogeneous and heterogeneous, light‐driven hydrogen evolution reaction (HER). We successfully deposited these catalysts by scanning electrochemical cell microscopy (SECCM) on supported and free‐standing 2D amino‐terminated carbon nanomembranes (CNMs) and quantified hydrogen by using Pd microsensors.